Evaluación del impacto de las políticas públicas del buen vivir en organizaciones agroproductivas solidarias de los cantones Jipijapa y Puerto López - Medina Zambrano, Génesis Nicole (2019)
The objective of this research is to evaluate the impact of public policies of good living in solidarity productive agro organizations of the Cantons Jipijapa and Puerto Lopez, with specific objectives such as: collect information from the existing theoretical basis, select the assessment indicators to measure the impact of public policies, to determine the current situation of the organizations of solidarity productive agro and finally to analyze the effects of public policies of good living; for the purpose of the investigation and on the basis of authors chose the indicators allowing to evaluate the impact of the PP in the OAPS, same as with the support of the survey on living conditions of the INEC (2013-2014) The questions were chosen in such a way that were applied to people with productive activities agro and fishing affiliated and non-affiliated to an organization, to perceive if you are fulfilling these policies. In order to facilitate a better understanding of the results of the surveys used the SPSS software "" itself that made it possible to carry out the tables where you specify which results to obtain an analysis understandable and efficient, based on these results an analysis concerning the level of compliance with the public policies of the BV summarized in a table where: 17 show a non-compliance, partial compliance 12 and 10 of effective compliance.